SIFAT MAMPU BASAH (WETTABILTY) SERAT BATANG MELINJO (GNETUM GNEMON) SEBAGAI PENGUAT KOMPOSIT MATRIKS EPOXY-RESIN - Chandrabakty, Sri (Jurnal MEKANIKAL, 2010)
This study aims to knowing the influence of surface treatment of fibers t wettability and adhesion ability melinjo bast fiber with epoxy-resin matrix. Wettability  had affected on mechanical properties of fiber reinforced composite. The research process was begun with providing treatment to the melinjo fiber surface, which is boiled with pure water and NaOH 5%  each for 60, 120 and 180 minutes. Contact angle specimen test conducted by dripping droplets of matrix on a single fiber, then the contact angle that occurs is measured using Image Pro Analyzer software (IPWin) through photographs taken by using optical microscope. The results showed that the largest  average of contact angle is  untreated fiber (42.37°) and the lowest is  media treatment of NaOH 5% (33.14°).